2004
DOI: 10.1016/j.jacc.2004.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Exercise acutely increases circulating endothelial progenitor cells and monocyte-/macrophage-derived angiogenic cells

Abstract: Our study demonstrates that exercise can acutely increase EPCs and CACs. Given the ability of these cell populations to promote angiogenesis and vascular regeneration, the exercise-induced cell mobilization may serve as a physiologic repair or compensation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
203
3
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(225 citation statements)
references
References 17 publications
10
203
3
9
Order By: Relevance
“…Our protocol can identify CD34À ECs (4) Incorrect gating strategy: Analyzing only CD45À cells leads to the exclusion of possible CD45+ ECs. ECs are evaluated as progenitors, which resemble lymphocytes, and so cells in the lymphocyte region in FS and SS are gated during flow cytometry [26,30]. This approach might cause the exclusion of ECs with different morphologic features, as we saw with our data showing variable EC size and morphology.…”
Section: Discussionmentioning
confidence: 91%
“…Our protocol can identify CD34À ECs (4) Incorrect gating strategy: Analyzing only CD45À cells leads to the exclusion of possible CD45+ ECs. ECs are evaluated as progenitors, which resemble lymphocytes, and so cells in the lymphocyte region in FS and SS are gated during flow cytometry [26,30]. This approach might cause the exclusion of ECs with different morphologic features, as we saw with our data showing variable EC size and morphology.…”
Section: Discussionmentioning
confidence: 91%
“…Here we studied circulating EPCs expressing an endothelial marker (VEGFR-2/VE-cadherin) and a haemopoietic stem cell or bone-marrow-derived marker (CD34/CD133), and also circulating progenitor cell subtypes expressing haemopoietic stem cell markers alone (CD34/CD133) [7,[11][12][13][14][15]17]. We found significant reductions in circulating cell counts of some populations of both classes of cells (endothelial progenitor, circulating progenitor cell subtypes) in young people with type 1 diabetes without any macrovascular disease or microalbuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…EPCs are a heterogeneous population characterised by the expression of surface markers of endothelial (vascular endothelial [VE]-cadherin [also known as CD144], vascular endothelial growth factor receptor 2 [VEGFR-2], CD31 and von Willebrand factor) and haemopoietic progenitor (CD34, CD133) lineages [7,[11][12][13][14][15][16]. Circulating EPCs consist of cells at various stages of maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies showed that a symptom-limited treadmill or bicycle exercise test could acutely increase the amount of EPCs. Possible mechanisms for this fast increase in EPCs (10 min to 2 h) may be an exercise-induced increase of VEGF (8,72) or exerciseinduced changes in shear stress, resulting in mobilization of the cells (73). Since all these studies investigated the effect of a single exercise bout on the mobilization of EPCs, one has to ask the question if ET over a longer time period also can influence the number and function of EPCs.…”
Section: Physical Exercisementioning
confidence: 99%